Pemetaan bahaya gempabumi deterministik dengan pendekatan Peak Ground Acceleration (PGA) di Kota Padang (Mapping of deterministic earthquake hazards using the Peak Ground Acceleration (PGA) approach in the city of Padang ) - Zaimi Netrisa; - Syafriani; Rahmat Triyono; Hamdi Arifin (Department of Physics – Universitas Negeri Padang UNP, 2018)
Indonesia is passed by three plates of the E urasia plate, the Indo-Australin plate and the Pasific plate. Along the west of Sumatera, south of Java, south of Nusa Tenggara, ending in the Banda Sea, the Eurasia plate and Indo-Australian plate, the Eurasia plate and the Pasific plate in the Maluku Sea and ending in the Banda Sea. West Sumatra’s mainland section has occurred a significant and damaging earthquake of 6time. The city of Padang is adjecent to the Indo-Australian plate meeting and the Eurasian Plate. DSHA method basically aims to develop an earthquake scenario that is determined by the distance ang magnitude that affect the location. The resulting ground vibration with the predetermined earthquake event parameters is than calculated using the attenuation equation in some cases. DSHA has a basic concept to determine the ground motion parameters by using the maximum earthquake magnitude and distance of earthquake source closest from the point of obsevation. Based on the mapping results on th map of Padang City has the level of prone divided into three categories of danger that is small, medium and large denger and soil conditions are soft, medium and hard. Minor hazard are in BRI, SMO dan ADS. The danger is in Lap.Imam Bonjol, GOV and Kampung Cina and great danger of being in GOR,UNP, APT, SRC, ORG and CMN. The PGA value is proportional to the differene in soil. The greater the value of PGA then the greater the intensity caused by the earthquake. In this study instead,